PENGARUH KUALITAS LAYANAN DAN KEPERCAYAAN TERHADAP LOYALITAS NASABAH PADA BAITUL MAAL WAT TAMWIL (BMT) SURYA BAROKAH - Welta, Fretty (I-Economics, 2017)
Consumer loyalty is very important for the company to maintain its survival and sustainable business activities. Customer loyalty in the use of services offered can be used as input to the company to improve and enhance the quality of services offered feed all and trust. This study aimed to analyzes the impact of service quality on customer loyalty and trust.  This study used a multiple linear regression analysis using SPSS. The population used is the customers 410 people. While the sample used as many as 40 people with the sample selection slovin model.  The results showed that the quality of service and trust affects customer influence on customer loyalty.